2021
DOI: 10.1002/cl2.1151
|View full text |Cite
|
Sign up to set email alerts
|

Court‐mandated interventions for individuals convicted of domestic violence: An updated Campbell systematic review

Abstract: Executive Summary/Abstract Background Survey research and analysis of police records, hospital emergency rooms, and women's shelters have clearly established the severity of the intimate partner violence problem and the need to find programs to address this issue. Roughly 1 in 4 women in an intimate relationship is a victim of intimate partner violence. Court‐mandated batterer intervention programs (BIPs) have been implemented throughout the United States as a leading method to address this problem. These prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…Another systematic review of court-mandated programs, found a modest but nonsignificant mean effect in favor of the program when outcome were based on official reports. However, the overall mean effect based on victim reports were either no difference or in favor of the no treatment condition, leaving the authors to determine that there is insufficient evidence to conclude that these programs are effective (Wilson et al, 2021). In sum, although the overall results are in a positive direction, it seems there is still some uncertainty as to the general efficacy of such court mandated programs, especially regarding the psychoeducational Duluth based models (Miller et al, 2013;Karakurt et al, 2019;Arce et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review of court-mandated programs, found a modest but nonsignificant mean effect in favor of the program when outcome were based on official reports. However, the overall mean effect based on victim reports were either no difference or in favor of the no treatment condition, leaving the authors to determine that there is insufficient evidence to conclude that these programs are effective (Wilson et al, 2021). In sum, although the overall results are in a positive direction, it seems there is still some uncertainty as to the general efficacy of such court mandated programs, especially regarding the psychoeducational Duluth based models (Miller et al, 2013;Karakurt et al, 2019;Arce et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years various treatment approaches based on different theoretical frameworks, settings and formats have been developed in an effort to stop and prevent partner violence, especially male-to-female IPV. The majority of these interventions have been based within a criminal justice context, where men convicted of domestic violence are mandated to attend a group-based batterer intervention program (e.g., Eckhardt et al, 2013;Wilson et al, 2021), constituting a combination of legal sanctions and therapeutic interventions. Although these programs vary in their methodology and stated goals, the majority have their origins in the Duluth model grounded in a sociocultural feministic framework evolving around men's attitudes and use of power and control (Pence and Paymar, 1993;Pence, 2002;Gondolf, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Arias et al, 2013; Arce et al, 2020), where the “other” categories are comprised of such heterogeneous samples of different treatment modalities that it is not possible to assess differential effectiveness by program type. This problem is confounded by many of the programs consisting of a blend of techniques from different modalities (Wilson et al, 2021), complicating a situation where the distinction between Duluth and CBT treatment programs was already unclear. Nevertheless, Miller et al (2013), in their review of 11 studies in the United States and Canada that rigorously evaluated the effect of IPV group‐based treatment for male offenders on recidivism, found that six studies that tested the effectiveness of Duluth‐like treatments had no effect on DV recidivism, whereas the five other studies of non‐Duluth group‐based treatments collectively reduced recidivism by 33%.…”
mentioning
confidence: 99%
“…More recently published reviews and meta‐analyses of controlled studies of IPV interventions (Arce et al, 2020; Arias et al, 2013; Cheng et al, 2019; Eckhardt et al, 2013; Karakurt et al, 2019; Miller et al, 2013; Travers et al, 2021; Wilson et al, 2021) have continued to find that in general the evidence for their effectiveness is inconclusive. The majority of trials included in these reviews were of interventions that were based on Duluth and/or CBT models and delivered in a group format.…”
mentioning
confidence: 99%
See 1 more Smart Citation